PENGARUH PENGGUNAAN APLIKASI DESKRIPEDIA BERBASIS GUIDED WRITING TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VI SEKOLAH DASAR - Wigena, Nezar Raksa; Gusrayani, Diah; Djuanda, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing is one of the essential skills in Indonesian language learning at the elementary school level. However, many students still struggle to write descriptive texts in a complete and structured manner. This issue arises from the suboptimal use of learning media and the lack of explicit guidance from teachers during the writing process. This study aims to examine the effect of using the Deskripedia application, which is based on guided writing, on the descriptive writing skills of sixth-grade elementary school students. This research employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The subjects consisted of 30 sixth-grade students from SDN Pasirjati. The main instrument used was a descriptive text writing test, assessed based on text structure and linguistic features. Data were analyzed using the Wilcoxon Signed-Rank Test and N-Gain score. The results showed a significant improvement in students’ writing skills after using Deskripedia, with the average score increasing from 36.63 (pretest) to 85.30 (posttest). The Wilcoxon test revealed a significance value of 0.000 (< 0.05), and the mean N-Gain score of 76.74 indicated a high category of improvement. These findings suggest that Deskripedia is an effective digital learning medium for enhancing students’ writing skills in a structured and independent manner.